New efficient, practical method for producing ‘Compreg’ OPW through integrated objective approach - Bakar, Edi Suhaimi; Abare, Al-Hasan Yakubu; Yong, Adrain C. C.; Ashaari, Zaidon (2014)
Oil palm wood (OPW) has been seen as alternative for the dwindling forest wood. Having inferior quality, OPW need to be processed and treated properly before it can be used as solid wood. The 5-step processing method was developed by Bakar et al (2004) that capable to solve all imperfections of OPW, producing high performance ‘compreg’ OPW. The process, however, is too long and considered as difficult by many practitioners. A new efficient and practical method with an integrated objective approach has been recently developed also by Bakar et al (2014). The 6-step process (Sawing – Compressing – Drying – Resin soaking – Heating – Hot-pressing) is much faster and easier than the 5-step method, producing comparable ‘compreg’ OPW in properties. The trunk is debarked with a peeler before being sawn by a modified sawing pattern (reverse cant sawing) which is no longer intended for producing square OPW but waney OPW timbers. OPW is not dried in the usual manner, but is first compressed to a certain extent so that the initial MC is forcibly reduced and creates micro-cracks. These quicken the drying by at least a factor of 10 (from 30-35 days to 3 days) without concern on excessive drying defects. The formation of micro-cracks facilitates resin introduction that can be carried out by a simple soaking instead of impregnation, and quicken the heating process by at least a factor of 3 (from 5-8 hours to 24-30 hours). Overall, this new patented method (PI 2014700947) is 8-10 times faster and simplifies the whole process.